THE INFLUENCE OF THE INSTITUTE OFCONTROL ON THE GROSS DOMESTIC PRODUCT OF THE COUNTRY - Dovha, Marharyta (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The article examines the influence of the activity of the control institute on the state of the gross domestic product of the country through a consistent analysis. Initially, the differentiation of public financial control agents is considered and the feasibility of analyzing the entities of public financial control in comparison with quasi-entities is substantiated. It is determined that two entities, namely the Accounting Chamber of Ukraine and the State Audit Office of Ukraine, are subject to control. Official reports of the State Audit Service, which are public and reflect the results of the activity of this structure over a long period of time, were used for consideration. In order to achieve this goal, it was established that there is a need to identify the presence or absence of correlation between the given indicators by means of correlation analysis. To test the model for usability, a determination factor of R2 was calculated, which shows how much these factors describe the model and what percentage is described by the unaccounted factors. In order to assess the adequacy of the studied model. Fisher’s analysis was performed. The significance of the parameters was estimated using the t-test. According to the results of verification of these indicators, it was determined that the model is adequate to experimental data and can be used for further analysis. To evaluate the quality of the model, the coefficient of elasticity Eb was calculated. On the basis of the conducted research the positive effect of the activity of the control agents, in part of the reimbursed expenses, on the economic state of the country due to the growth of the gross domestic product is revealed and the necessity of enhancing the efficiency of their activity is substantiated, that will have a positive effect on the economic situation.